PENGARUH TEKNOLOGI INFORMASI TERHADAP PERKEMBANGAN PROFESI AKUNTANSI DI INDONESIA - Rina Asmara (Jurnal Akuntansi Bisnis, 2017)
Numerous events have influenced the dynamics of accounting profession in the world, including in Indonesia. The emergence and development of accounting profession is caused by events such as the exposure of accounting scandal on large companies all over the world (WorldCom, Xerox, Tyco, etc.), and the fall of internationally certified public accountant office, Arthur Andersen, which has triggered the regulation of Sarbanes-Oxley Act of 2002 in the United States. Moreover, it has been noted that numerous governmental organizations are not quite ready to manage recent public finance. In addition, many governmental apparatus do not have proper accounting background to conduct the operation. More people feel the need for information as one of the principle commodity. For that matter, people start to look for and create systems and tools to communicate, such as drawing simple pictures in a cave, painting, using hand signals, smoke signals, voice signals, letters, words, sentences and recently, by using telephone and internet. The tools and systems created is later known as Information Technology, or commonly abbreviated into IT.Keyword : Teknologi Informasi, Profesi Akuntansi